The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1161/circimaging.112.980797
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Diagnostic and Prognostic Value of Contemporary Stress Echocardiography in a Chest Pain Unit

Abstract: P atients presenting to the emergency department (ED) with chest pain represent a significant healthcare burden; the estimated annual cost to the US economy is $10 to $12 billion.1 A large proportion of ED admissions are patients with suspected acute coronary syndrome (ACS) but with a nondiagnostic ECG and a normal 12-hour troponin, although fewer than half are subsequently diagnosed with ACS.2 A retrospective study found that the mean cost per patient was ≈$3200, with 73% of cost attributable to admission tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 23 publications
1
34
1
5
Order By: Relevance
“…These findings are in contrast to SE studies performed in younger populations 4 5. CKD is highly prevalent in elderly populations (23% of our population) and forebodes worse outcomes, with predialysis patients having nine times higher death rates in comparison to population controls 12 13.…”
Section: Discussioncontrasting
confidence: 87%
“…These findings are in contrast to SE studies performed in younger populations 4 5. CKD is highly prevalent in elderly populations (23% of our population) and forebodes worse outcomes, with predialysis patients having nine times higher death rates in comparison to population controls 12 13.…”
Section: Discussioncontrasting
confidence: 87%
“…Obrazowanie obciążeniowe jest preferowane w stosunku do elektrokardiograficznej próby wysiłkowej ze względu na większą dokładność diagnostyczną [63]. W różnych badaniach wykazano, że prawidłowy wynik echokardiografii obciążeniowej (wysiłkowej, dobutaminowej lub z dipirydamolonem) ma wysoką, ujemną wartość predykcyjną dla niedokrwienia i wiąże się z doskonałymi wynikami klinicznymi u pacjentów [64,65]. Co więcej, echokardiografia obciążeniowa wykazuje większą wartość prognostyczną niż próba wysiłkowa EKG [64,66].…”
Section: Ocena Czynnościowaunclassified
“…W różnych badaniach wykazano, że prawidłowy wynik echokardiografii obciążeniowej (wysiłkowej, dobutaminowej lub z dipirydamolonem) ma wysoką, ujemną wartość predykcyjną dla niedokrwienia i wiąże się z doskonałymi wynikami klinicznymi u pacjentów [64,65]. Co więcej, echokardiografia obciążeniowa wykazuje większą wartość prognostyczną niż próba wysiłkowa EKG [64,66]. Zastosowanie kontrastu może poprawić wizualizację granic wsierdzia, co potencjalnie zwięk-sza szansę wykrycia niedokrwienia [67].…”
Section: Ocena Czynnościowaunclassified
“…A recent observational study involving almost 900 patients presenting with acute chest pain demonstrated that diagnostic image quality was feasible in almost 99% (contrast ultrasound agent was used in 52% of these patients with unselected BMI) with optimal prognostic outcome 5. Guidelines endorse the use of contrast during SE for improved reader confidence and study accuracy 6 7…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, we recently reported a feasibility for diagnostic images of >99% in consecutive patients presenting with acute chest pain using state-of-the-art SE techniques as described above 5. We hypothesised that contrast-enhanced SE will be a useful technique for implementing an optimal management strategy in obese patients presenting with suspected angina.…”
Section: Introductionmentioning
confidence: 99%